Atrial imaging and cardiac rhythm in cryptogenic embolic stroke: a preliminary analysis of the ARIES study. (19th May 2022) - Castrejon Castrejon, S; Rigual, R; Fernandez-Gasso, L; Martinez-Cossiani, M; Garcia-Castro, J; Ruiz-Ares, G; Rodriguez-Pardo, J; De Celis, E; Casado, L; Alonso De Lecinana, M; Diez-Tejedor, E; Perez-David, E; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cryptogenic stroke is frequently related to cardioembolic source previously unknown. We aim to analyze atrial fibrillation (AF), parafibrilatory status (para-AF) and echocardiographic signs of atrial dysfunction in patients (p) with cryptogenic stroke. Methods: Consecutive p with cryptogenic stroke were prospectively enrolled in the on-going study ARIES (Atrial Imaging and cardiac Rhythm In Embolic Stroke). Cardiologic work-up includes external wearable 2-lead ECG monitoring system for 30 days (non-AF, AF, para-AF defined as >3000 atrial ectopic beats/day or >2 "micro-AF" episodes (fibrillatory burst <30 s)/day) and advanced left atrial echocardiography (signs of atrial dysfunction as strain during three phases -reservoir, conduit, and contractile-). The first monitoring was started before hospital discharge, p without AF in the first monitoring and without extremely disabling neurologic sequelae underwent a further 30 days monitoring. We describe stroke recurrence at 90 days follow-up, and we compare echocardiographic signs of atrial dysfunction according to rhythm study. Results: 78 p completed follow-up (72±12 yo, 53% females). AF was diagnosed in 27 (34%) p: 22/78 (28%) in the first monitoring and 5/43 (12%) in the second one. para-AF was diagnosed in 22/51 (43%) non-AF p. Other arrhythmias: sustained (>30 s) focal atrial tachycardia documented in 4/51 (8%) non-AF p, AVNRT in 1/51 (2%) non-AF p, advanced AV block in 1/78 (1%) p. Worse left atrial mechanical properties were demonstrated in p with para-AF compared to non-AF p (reservoir strain 22.2±9.8 vs 32.8±12, p=0.004; conduit strain -9.6±4.8 vs -14.4±9, p=0.008; contractile strain 12.6±4.8 vs 17.9±7.8, p=0.025), without significative differences compared to AF p. There were three stroke recurrences (3.8%), 2/3 in para-AF p. Conclusion: In this preliminary analysis, patients with cryptogenic stroke presented AF in 34% and para-AF in 28%. Para-AF patients show significative atrial dysfunction in echocardiography and more stroke recurrences. A longer follow-up is required to confirm these findings.